Effects of erector spinae plane block versus local infiltration analgesia for abdominal surgeries: a protocol for systematic review and meta-analysis - Jing Li; Feng Chen; Yiyong Wei; Shoujia Yu (BMJ Open)
Introduction Erector spinae plane (ESP) block and local infiltration analgesia (LIA) are widely used to control postoperative pain after abdominal surgery. An increasing number of randomised controlled trials (RCTs) have compared the analgesic effects of ESP block and LIA after abdominal surgery, but the results are inconsistent. This protocol of a systematic review and meta-analysis aims to determine whether the analgesic effects of ESP block are better than those of LIA in abdominal surgeries.Methods and analysis Two authors will independently search PubMed, EMBASE, Web of Science and the Cochrane Library from their inception to 15 August 2025. RCTs that compared the analgesic effects of ESP block with LIA for abdominal surgeries will be included. The primary outcome will be opioid consumption over 24 hours postoperatively. The secondary outcomes will include the time to first rescue analgesia, pain intensity score and incidence of adverse effects. RevMan V.5.4 software will be used for statistical analysis.Ethics and dissemination Ethical approval is not applicable. The results of this study will be publicly published in one peer-reviewed journal.PROSPERO registration number CRD42024598176.